CD62-mediated activation of platelets in cerebral white matter lesions in patients with cognitive decline. (January 2016) - Kuriyama, Nagato; Mizuno, Toshiki; Yasuike, Hiromi; Matsuno, Hiroyuki; Kawashita, Eri; Tamura, Aiko; Ozaki, Etsuko; Matsui, Daisuke; Watanabe, Isao; Koyama, Teruhide; Miyatani, Fumitaro; Kondo, Masaki; et al.
Highlights: Expressions of CD62P on circulating platelets were observed in patients with increasing grades of cerebral deep white matter lesions (DWMLs). The multivariate analysis for higher CD62P values showed that the odds ratio in the high-grade DWMLs group was 3.03 compared with the low-grade DWMLs group. CD62P levels could be useful as an additional clinical marker for the early detection of DWML-related cognitive decline. Abstract: Background: Vascular dementia is related to intracranial arteriosclerosis associated with deep white matter lesions (DWMLs). DWMLs have been linked to thrombogenesis due to sustained platelet activation; therefore, an accurate hematological marker is needed. This study was done to evaluate the usefulness of a new method to examine the function of activated platelets in order to assess DWMLs associated with cognitive decline. Methods: A total of 143 individuals (70.4 ± 6.1 years old) who underwent hospital-based health screening using head MRI were evaluated. DWLs were evaluated on T2-weighted and FLAIR images by semi-quantitatively grading them from Grade 0 (none) to Grade 3 (severe) using the Fazekas classification. Cognitive function was evaluated using the MMSE and the word fluency test. Platelet activation was assessed using fluorescence-labeled anti-human platelet monoclonal antibodies and semi-quantitatively determining PAC-1- and CD62P-positive rates by flow cytometry. Results: Significant increases in hypertension and CD62P levels were observed with increasing DWML grade (2.6% in Group 0, 3.1% in Group 1, 4.1% in Group 2, and 5.0% in Group 3). CD62P levels were defined as elevated when they were above the mean + 2SD of the Grade 0 group, and the odds ratio of the Grade 2 + 3 group was 3.03. A significant negative correlation was observed between CD62P levels and word fluency tests or the MMSE score. Conclusion: Elevations in CD62P levels, which reflect platelet function activation, were associated with white matter lesions accompanied by a decline in cognitive function. CD62P levels may be useful as a sensitive clinical marker for the early detection of DWMLs with cognitive decline.